The Three Ps: Psychiatry, Pharmacy, and Pharmacogenomics, a Brief Report From New Zealand - Maggo, Simran D.S.; Sycamore, Kyra L.V.; Miller, Allison L.; Kennedy, Martin A. (Frontiers in Psychiatry, 2019)
We describe a case series of 22 individuals who were referred to our laboratory by a pharmacist based in a mental health hospital, for pharmacogenetic analysis due to severe or unexpected adverse drug reactions (ADR) to psychiatric medication. The participants were genotyped for common variation in the CYP2D6, CYP2C19 and CYP2C9 genes, using Sanger sequencing. We tested variants in these genes as they have the strongest evidence with respect to altering the pharmacokinetics of commonly prescribed psychiatric medicine. Looking specifically at the subset of 18 European study participants, we observed a high but non-significant rate of pharmacogenetic variants, compared to allele frequency from unselected population samples. For CYP2D6 we observed an elevated frequency of both poor (17%) and intermediate (33%) metabolizers when compared with previously reported frequencies (6% and 12% respectively). For CYP2C19 we observed an increased frequency of intermediate (33%) and ultra-rapid (17%) metabolizers compared to expected frequencies (21% and 4% respectively). While sample size is a major limitation of this brief report, we can conclude that patients with adverse reactions to antidepressant or antipsychotic drugs selected by a specialist mental health pharmacist appear to have a relatively high rate of genetic variants in pharmacogenes known to affect the pharmacokinetics of these drugs. The selective application of such pharmacogenetic tests by clinical pharmacists may be a valuable approach to clarify the basis for adverse or unusual responses to medication, and to guide ongoing prescribing decisions for this group of patients.